High speed computation of muscle stress problem using crack propagation modelling on DPCs platform - Alias, Norma (American Scientific Publishers, 2014)
Muscle stress is a disease resulting from performing too much effort, sport fitness or high blood pressure problem. This paper focuses on the mathematical modeling of crack propagation that applies on the human muscle stress. The modeling describes the relationship between the temperature and crack propagation among targeted region, node and element. The contribution of this paper is to predict the stress level based on the mathematical modeling for nodal displacements of crack propagation with respect to time and space. The initial stage of crack propagation that leads to an initiation of crack propagation is being modeled satisfactorily the discretization of finite element method (FEM) of the specific region. The sequential algorithm of the crack propagation simulation for muscle stress will be solve using Gauss Seidel method (GS). The parallel algorithm will be solve using Red Black Gauss Seidel method (RBGS). Some comparisons based on numerical analysis and parallel performance evaluation will be analyzed in terms of convergent rate of FE solution results to the exact solution of clinical dataset, run time prediction, time execution, speedup, efficiency, effectiveness and temporal performance. C and Parallel Virtual Machine (PVM) software with open source operating system on distributed parallel computer system (DPCS) will support the huge computation cost of the parallel algorithms.